2014
DOI: 10.1002/cncr.28728
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 trial of R1507, a monoclonal antibody to the insulin‐like growth factor‐1 receptor (IGF‐1R), in patients with recurrent or refractory rhabdomyosarcoma, osteosarcoma, synovial sarcoma, and other soft tissue sarcomas: Results of a Sarcoma Alliance for Research Through Collaboration study

Abstract: BACKGROUND Insulin‐like growth factor‐1 receptor (IGF‐1R) is implicated in the pathogenesis of rhabdomyosarcoma (RMS), osteosarcoma (OS), and synovial sarcoma (SS). The authors conducted a multi‐institutional phase 2 trial of the monoclonal antibody R1507 in patients with various subtypes of recurrent or refractory sarcomas. METHODS Eligibility criteria included age ≥2 years and a diagnosis of recurrent or refractory RMS, OS, SS, and other soft tissue sarcomas. Patients received a weekly dose of 9 mg/kg R1507 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
118
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(123 citation statements)
references
References 43 publications
3
118
0
2
Order By: Relevance
“…While conventional cytotoxics do improve survival in Ewing sarcoma, rhabdomyosarcomas, and osteosarcoma, they confer little curative benefit in most soft-tissue sarcomas, as confirmed by a recent analysis of 2,665 cases across 11 clinical trials (1). Much recent effort has gone into targeting expressed proteins in activated oncogenic pathways, but these have had disappointing results in phase II trials (2)(3)(4), and few sarcoma studies have progressed to phase III (5). Off-label use is common but has shown little evidence of efficacy (6).…”
Section: Introductionmentioning
confidence: 99%
“…While conventional cytotoxics do improve survival in Ewing sarcoma, rhabdomyosarcomas, and osteosarcoma, they confer little curative benefit in most soft-tissue sarcomas, as confirmed by a recent analysis of 2,665 cases across 11 clinical trials (1). Much recent effort has gone into targeting expressed proteins in activated oncogenic pathways, but these have had disappointing results in phase II trials (2)(3)(4), and few sarcoma studies have progressed to phase III (5). Off-label use is common but has shown little evidence of efficacy (6).…”
Section: Introductionmentioning
confidence: 99%
“…Three of eight (37%) ES/PNET specimens were defined as positive for IGF-1R in our study. Although studies with IGF-1R antibodies in ES/PNETs are limited or disappointing, there are assertions in the literature that IGF-1R inhibitors may play a role in the treatment of ES/PNETs since it is regarded as a key mechanism in proliferation (7,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1R is also involved in malignant tumor transformation and is overexpressed in a variety of human malignancies such as lung, prostate, breast, and colorectal carcinomas (2)(3)(4)(5). Studies have revealed a pronounced expression of IGF-1R in pediatric tumors, such as Ewing sarcoma/primitive neuroectodermal tumors (ES/PNETs), rhabdomyosarcomas (RMSs), osteosarcoma, and synovial sarcoma (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the preclinical anti-RMS activity of targeted agents such as mTOR inhibitors (Hosoi et al 1999) and neutralizing IGF1 receptor antibodies (Mayeenuddin et al 2010) have not translated thus far into durable objective response rates in early-phase clinical trials (Geoerger et al 2012;Pappo et al 2014;Weigel et al 2014). However, improved event-free survival of individuals with relapsed RMS after treatment with the mTOR inhibitor temsirolimus in combination with vinorelbine and cyclophosphamide supports experimental strategies involving combinations of targeted agents and established drugs (Mascarenhas et al 2014).…”
Section: Box 1 the Banbury Center At Cold Spring Harbor Laboratorymentioning
confidence: 99%